Psychoactive Substance Use and Problematic Internet Use as Predictors of Bullying and Cyberbullying Victimization - Zsila, Ágnes (Int J Ment Health Addict, 2017)
Research exploring the relationship between addictions and experiences of bullying suggests that problem behaviors may generally be associated with an increased risk of victimization. The aim of the present study was to examine the role of psychoactive substance use, excessive Internet use, and social support in both traditional offline bullying and online “cyberbullying” victimization in a nationally representative sample of adolescents (N = 6237; 51% male; M (age) = 16.62 years, SD = 0.95). Results demonstrated that traditional bullying victimization was associated with cyberbullying victimization. Furthermore, psychoactive substance use and problematic Internet use predicted both traditional bullying and cyberbullying victimization. Finally, perceived social support was found to be an important protective factor against both traditional and cyberbullying victimization. However, psychoactive substance use and problematic Internet use accounted for only a small proportion of variance in victimization.